1996
DOI: 10.1063/1.868867
|View full text |Cite
|
Sign up to set email alerts
|

NMR imaging of velocity profiles and velocity distributions in bead packs

Abstract: Spatially resolved velocity profiles and spatially nonresolved velocity distributions of steady flow in a tube and bead packs were measured. Two different NMR experiments were used to measure velocity distributions. In one, the velocity histogram was calculated from spatially resolved velocity phase encoded images acquired in a 6 mm bead pack. In the other, a Fourier flow method was used to measure the velocity distribution directly in a 0.25 mm bead pack. Axial velocity profiles in the pore space of the 6 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(105 citation statements)
references
References 18 publications
12
92
1
Order By: Relevance
“…The local counter diffusive flux, as well as the Darcy counter flow (Kutsovsky et al 1996;Maier et al 1998;Ogawa et al 2001;Li et al 2010), was observed in the present study (Figs. 9c, 11c).…”
Section: Negative Tail and Long Positive Tailsupporting
confidence: 54%
See 2 more Smart Citations
“…The local counter diffusive flux, as well as the Darcy counter flow (Kutsovsky et al 1996;Maier et al 1998;Ogawa et al 2001;Li et al 2010), was observed in the present study (Figs. 9c, 11c).…”
Section: Negative Tail and Long Positive Tailsupporting
confidence: 54%
“…(i) The local counter flow was already found for the Darcy flow (not diffusion) in porous media (Kutsovsky et al 1996;Maier et al 1998;Ogawa et al 2001;Li et al 2010). The local flux obeys the log-normal distribution for the random resistor network (de Arcangelis et al 1985) and for the Darcy flow (Cenedese and Viotti 1996;Lebon et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However for higher Re, e.g., Re = 4, their plots show a small plateau. This is also the case for results in Kutsovsky et al (1996) obtained with NMR. Here Re up to about 50 is studied and it is clear that the distribution profiles of u x (v z in their paper) attain a more plateau like shape as Re increases in accordance with our results.…”
Section: Detailed Studies Of the Flowmentioning
confidence: 74%
“…Both studies found an oscillatory radial velocity profi le. Kutsovsky et al 4 have been used a non-invasive Magnetic Resonance Imaging (MRI) experimental method to obtain local fl ow patterns in fi xed beds. The method has been restricted to low fl ow rates, Re < 100 and to fl uids which can produce a suitable signal for measurement.…”
Section: Introductionmentioning
confidence: 99%